FREQUENCY OF POST-TONSILLECTOMY SECONDARY HEMORRHAGE - Arif, Muhammad; Noor, Allah; Anwar, Khurshid; Khan, Saeed (Khyber Journal of Medical Sciences, 2025)
Objective: To determine the frequency of post-tonsillectomy secondary hemorrhage following tonsillectomy in patients with chronic tonsillitis. Subject and methods: This prospective & descriptive study was conducted at the ENT Department, Hayatabad Medical Complex, Peshawar from July 1, 2018, to December 31, 2019. A total of 287 patients were included in this study. A complete history and examination were carried out at the time of admission. A tonsillectomy was performed the next day. During the procedure, bleeding was controlled by ligation of the bleeders with silk suture. All the patients remained admitted & observed for 48 hours after tonsillectomy. After discharge, patients were instructed to visit the department of ENT in case of any bleeding per oral. All the post-tonsillectomy secondary hemorrhages till 2 weeks post-tonsillectomy were documented. Results: A total of 287 patients were included in this study with M:F ratio of 2:1 and a mean age of 18± 9.90 years. The highest number of patients was recorded in the age group 4-15 at 128 (44.59%). It was in the same age group in whom the highest number of patients seeking management for post-tonsillectomy secondary hemorrhage. Overall secondary hemorrhage was recorded in 17 (5.9%) of patients. Statistical analysis shows that gender and age did not significantly affect the occurrence of secondary hemorrhage. Conclusion: Post-operative secondary hemorrhage is a common complication of tonsillectomy patients and still poses a threat to both the patient and clinician when a good recovery has been made and the patient is discharged from the hospital.